2011
DOI: 10.1111/j.1365-2044.2010.06603.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing practice with changing research: results of two UK national surveys of intensive insulin therapy in intensive care patients*

Abstract: Summary We conducted two telephone surveys of all United Kingdom adult intensive care units in 2007/8 and 2010 to assess practice with regard to intensive insulin therapy for glycaemic control in critically ill patients, and to assess the change in practice following publications in 2008 and 2009 that challenged the evidence for this therapy. Of 243 units that had a written policy for intensive insulin therapy in 2007/8, 232 (96%) still had a policy in 2010. One hundred and six (46%) units had updated their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Perversely, this was one of the reasons why a bag of 0.9% saline with 5% glucose was available in the ICU where the incident reported by Gupta and Cook occurred, enabling the halfcovered bag to be misread as 0.9% saline only [1]. Furthermore, medical practice is constantly evolving [12] and so guidance has to change and evolve also. Given this, coupled with the endless creativity of human beings in finding new ways of working round and within complex systems, and the pure capriciousness of chance, it is no surprise that problems can still occur even when the guidance is followed and practice is 'optimal' [13,14].…”
Section: Editorialmentioning
confidence: 99%
“…Perversely, this was one of the reasons why a bag of 0.9% saline with 5% glucose was available in the ICU where the incident reported by Gupta and Cook occurred, enabling the halfcovered bag to be misread as 0.9% saline only [1]. Furthermore, medical practice is constantly evolving [12] and so guidance has to change and evolve also. Given this, coupled with the endless creativity of human beings in finding new ways of working round and within complex systems, and the pure capriciousness of chance, it is no surprise that problems can still occur even when the guidance is followed and practice is 'optimal' [13,14].…”
Section: Editorialmentioning
confidence: 99%
“…The term 'evidence-based medicine' is more recent and apparently first appeared in the medical literature in 1992, in a paper by Guyatt et al [3]. The survey in this issue by Paddle et al [4] illustrates how evidence can be rapidly incorporated into standard practice, but then, within a short time, be subject to reassessment and a change in routine management. The clinical study by Van den Berghe et al [5] was based upon good basic science, and showed a significantly lower mortality rate and number of complications in critical care patients given insulin targeted to achieve blood glucose values within a narrow range.…”
Section: Editorialmentioning
confidence: 99%
“…A number of factors are associated with peri-operative stroke: a preoperative history of stroke or transient ischaemic accident; prior use of clopidogrel or ticlopidine; significant perioperative bleeding; atrial fibrillation; clinically significant hypotension; renal disease; valvular heart disease; and urgent surgery following hip fracture [3][4][5]. Each of these may involve a potential pathway through which peri-operative stroke is precipitated when beta-blockers are administered.…”
Section: Editorialmentioning
confidence: 99%
“…Thus, about 46% of British ICUs changed their intensive glycemic control policy by adopting this target limit. 4 Current indications about the glycemic control range in critically ill patients do not preclude further multicenter studies, including a larger number of patients to define the ideal target range of blood glucose for intensive glycemic control at the best risk-benefit ratio. However, accurate glucose measurements and insulin administration protocols should be standardized to avoid heterogeneity in the outcomes.…”
Section: Introductionmentioning
confidence: 99%